USE OF INTELLEGENT AND BLOCK CHAIN TECHNOLOGIES IN INFORMATION MANAGEMENT Minsk Innovation University - U. A. Vishniakou (Системный анализ и прикладная информатика)
The aim of this work is the analysis of methods, approaches, technologies, means of information management (IM), using both conventional technologies and adding new intellectual and block chain. Trends in the use of intelligent technologies in information management are given. The developments in the field of intelligent agents based on semantic web, web-services and semantic web-services, the use of cloud computing (CC) are shown. The main ideas of semantic technologies, in which a page of the semantic network contains information in two languages: the natural and special, understood only by intelligent software agents (IA) are discussed.The use of block chain technology for the control of various material and non-material assets are done. Technically, the block chain technology is another application layer on top of the stack of the Internet protocols and can be integrated with the semantic level. The use of intelligent technologies in the information management in the cloud area with the work of IA. The intelligent web (web 3.0), which became the next stage in the development of the Internet is discussed. It forms the semantics on the ontology dase, creating new opportunities for IA to perform various user requests. Analyzes the major developments in the field of intellectualization of IM, and the main tendencies of their development. The result was a list of criteria and their values, which must meet an intelligent system for IM.As trends in the development of IM is considered the improvement of models and methods of joint activity of IA in the cloud area using block chain technology. Three directions of development of intellectual control system are proposed. As the development of information management proposed the creation of an instrumental platform based on multi agent approach, integrating semantic and block chain technology in the cloud area.